Understanding the contribution of malaria parasites to continued residual malaria in a pre-elimination setting in South Africa : implications for elimination strategies - Birkholtz, Lyn-Marie (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.